(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
Abstract This research discusses acts of terrorism as crimes against humanity from the perspective of international criminal law and the jurisdiction of the International Criminal Court (ICC). Terrorism is considered an extraordinary crime of a transnational nature that violates universal human rights values. Although a global definition of terrorism has not yet been agreed upon, various international conventions have recognized terrorism as an international crime. The Rome Statute provides a legal framework for classifying terrorism as a crime against humanity when committed systematically and widely against civilians. This research uses a normative juridical method by analyzing positive legal norms, principles of international law, and legal doctrines relevant to the crime of terrorism. The research results show that the ICC has four types of jurisdiction in handling terrorism cases: personal jurisdiction (over individuals), criminal jurisdiction (over serious crimes), territorial jurisdiction (over states parties to the Rome Statute), and temporal jurisdiction (over crimes committed after the enactment of the Statute).The ICC plays an important role in the prosecution, trial, and protection of terrorism victims, but it can only fulfill its duties if the relevant countries are unable or unwilling to prosecute the perpetrators. It is recommended that the international community encourage the global harmonization of the definition of terrorism, increase the number of countries ratifying the Rome Statute, and strengthen international cooperation in law enforcement and the implementation of ICC rulings related to terrorism crimes. Keywords: Terrorism, Crimes Against Humanity, International Criminal Law, ICC Jurisdiction, Rome Statute. Abstrak Penelitian ini membahas tindak pidana terorisme sebagai kejahatan terhadap kemanusiaan dari perspektif hukum pidana internasional dan yurisdiksi Mahkamah Pidana Internasional (ICC). Terorisme dianggap sebagai kejahatan luar biasa yang bersifat transnasional dan melanggar nilai-nilai hak asasi manusia yang bersifat universal. Meskipun definisi terorisme secara global belum disepakati, berbagai konvensi internasional telah mengakui terorisme sebagai kejahatan internasional. Statuta Roma menyediakan kerangka hukum untuk mengklasifikasikan terorisme sebagai kejahatan terhadap kemanusiaan ketika dilakukan secara sistematis dan meluas terhadap penduduk sipil. Penelitian ini menggunakan metode yuridis normatif dengan menganalisis norma hukum positif, prinsip-prinsip hukum internasional, serta doktrin hukum yang relevan dengan tindak pidana terorisme. Hasil penelitian menunjukkan bahwa ICC memiliki empat jenis yurisdiksi dalam menangani kasus terorisme: yurisdiksi personal (terhadap individu), yurisdiksi kriminal (terhadap kejahatan berat), yurisdiksi teritorial (negara-negara pihak Statuta Roma), dan yurisdiksi temporal (kejahatan setelah pemberlakuan Statuta). ICC memiliki peran penting dalam penuntutan, pengadilan, dan perlindungan korban terorisme, tetapi hanya dapat melaksanakan tugasnya jika negara terkait tidak mampu atau tidak bersedia mengadili pelaku. Disarankan agar komunitas internasional mendorong harmonisasi definisi terorisme secara global, memperbanyak negara yang meratifikasi Statuta Roma, serta memperkuat kerja sama internasional dalam penegakan hukum dan pelaksanaan putusan ICC terkait kejahatan terorisme. Kata kunci: Terorisme, Kejahatan terhadap Kemanusiaan, Hukum Pidana Internasional, Yurisdiksi ICC, Statuta Roma.